Macro-Propagation of Kakarsinghi (Pistacia integerrima)through Air - Layering - Bahar, Nawa (Indian Forester, 2024)
Poor seed setting, low germination per cent, infertility and rooting in branch cuttings are some of the difficulties in the Kakarsinghi (Pistacia integerrima) species. Therefore, Macro -propagation technique through air -layering was developed for mass multiplication of this threatened species which has been found cost - effective, eco - friendly and innovative.